Analisis Problematika Guru Dalam Mengimplementasikan Kurikulum Merdeka Di SDN Inpres 2 Koya Timur - Adawiyah, Rabiatul; Denny Aulia Rachmawati (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
Along with the advancement of time, the educational curriculum in Indonesia has undergone various changes and updates, now referred to as the Merdeka Curriculum. This research aims to identify and analyze the challenges faced by teachers in implementing the Merdeka Curriculum at SDN Inpres 2 Koya Timur. Several challenges are encountered by teachers, especially in remote areas such as Koya Timur, namely: 1) teacher capacity building and training, and 2) strengthening stakeholder support and involvement. The research method employed is a qualitative approach with a case study research design. The researcher used data collection techniques including observation, interviews, and questionnaires. The subjects of this research consist of 20 class teachers, including the principal of SDN 2 Inpres Koya Timur, Papua, determined using a focus group discussion (FGD) sampling technique. The results of this study conclude that the readiness of teachers in implementing the Merdeka Curriculum is still varied, thus requiring special attention. Strategies to improve teacher readiness through continuous professional development, mentoring, and teacher collaboration have proven effective. Teacher readiness has significant implications for the success of the Merdeka Curriculum implementation.